Parental nicotine replacement therapy and offspring bronchitis/bronchiolitis and asthma – a nationwide population-based cohort study - Molero, Y; Zetterqvist, J; Lichtenstein, P; Almqvist, C; Ludvigsson, J (Dove Medical Press, 2018)
Background: Prior evidence shows that environmental tobacco smoke is a risk factor for respiratory tract infections, wheeze, and asthma. Nicotine replacement therapy has been shown to increase smoking cessation. However, no prior studies have explored if parental use decreases the risk of bronchitis/bronchiolitis and asthma in the offspring. Objective: To examine whether nicotine replacement therapy varenicline, given to parents, was associated with a reduction in bronchitis/bronchiolitis and/or asthma in their children. Methods: This study is a population-based cohort study, linking data from nationwide registers, and using a within-individual design that minimizes selection effects and controls for time-invariant confounding factors. Participants included 37,420 parents with a collected prescription of varenicline with 72,392 offspring <18 years of age. Exposure was defined as collected prescriptions of varenicline among the parents. Primary outcomes were offspring hospital visits for bronchitis/bronchiolitis (ICD10: J20 or J21) and offspring hospital visits for asthma (ICD10: J45). Results: Parental varenicline treatment was associated with a lower rate of visits for bronchitis/bronchiolitis in their children (incidence rate ratio [IRR]=0.67; 95% CI=0.50–0.91), but no association was found for asthma (IRR=1.08; 95% CI=0.97–1.19). The rate reduction of bronchitis/bronchiolitis was similar when we restricted data to children aged 0–3 years (IRR=0.71; 95% CI=0.52–0.97) and to maternal varenicline treatment (IRR=0.64; 95% CI=0.43–0.96). When restricting the outcomes to unplanned visits only (ie, excluding booked appointments, follow-ups, and referrals), no associations were found (IRR=0.72, 95% CI=0.51–1.02). Conclusion: In this cohort study, nicotine replacement treatment in parents was associated with reduced hospital visits for bronchitis/bronchiolitis in their children.